2020
DOI: 10.1111/ajpy.12291
|View full text |Cite
|
Sign up to set email alerts
|

Follower‐rated leadership styles, leader behaviours, and leaders' thinking styles: A test of the cognitive experiential leadership model

Abstract: Objective: The Cognitive Experiential Leadership Model (CELM) predicts that leaders' thinking styles will be related to transformational leadership and effective leadership behaviours, especially influencing tactics and conflict handling styles. However, most of the existing evidence for this model comes from studies that have used self-report methods where self-presentational biases may influence the studies' results. Moreover, there is incomplete evidence for the proposed connections in this model between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(71 reference statements)
1
5
0
Order By: Relevance
“… Curtis et al (2017) did not find a significant relationship between self-rated emotionality and self-rated transformational leadership in either of their studies. However, Curtis (2020) found that other-rated emotionality and other-rated transformational leadership correlated significantly, albeit weakly.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“… Curtis et al (2017) did not find a significant relationship between self-rated emotionality and self-rated transformational leadership in either of their studies. However, Curtis (2020) found that other-rated emotionality and other-rated transformational leadership correlated significantly, albeit weakly.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, two previous studies have found correlations between self-rated transformational leadership and leaders’ preferences for imaginative thinking ( Curtis et al, 2017 ). Moreover, in the one study, where followers rated both thinking styles and leadership styles, transformational leadership was positively correlated the rational thinking, imagination, and emotionality ( Curtis, 2020 ). These previous studies, also found correlations between self-rated transformational leadership and behavioral coping, and two previous studies ( Atwater and Yammarino, 1993 ; Dubinsky et al, 1995 ) have also found correlations between behavioral coping and other-rated transformational leadership.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transformational leadership style is becoming more and more necessary, which also means that leaders need to be creative and flexible in how to inspire employees to give their best, in ways to support employees to develop their intellectual power to an advanced level. Curtis (2020) [53] shown that transformational leadership style and leadership thinking are closely related to leadership performances, especially affecting tactics and conflict-handling styles in leadership activities. Curtis et al (2017) [54] suggested that leadership performance depends quite closely on the relationship between leadership thinking and transformational leadership style.…”
Section: -3-relationship Between Transformational Leadership Style and Leadership Thinkingmentioning
confidence: 99%